The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1981-6723.2416
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial properties of ethanolic extracts of guarana, boldo, rosemary and cinnamon

Abstract: In this investigation, the ethanolic extracts of two less known plants, little reported in the literature (guarana and boldo leaves) were studied in comparison with the ethanolic extracts of two well studied plants (cinnamon and rosemary), regarding their colour, GC-MS profile, phenolic content and their antioxidant and antimicrobial properties. The rosemary (59.20 ± 0.28) and guarana (56.63 ± 0.54) extracts showed the highest values for luminosity (L*) and the UV-Vis absorption increased when L* decreased. GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
1
16
1
Order By: Relevance
“…Moreover, Bonilla & Sobral () developed and characterised active films based on gelatin:chitosan blends, incorporating Boldo extract, at 1%. The first study confirmed six main compounds (1,8‐cineol, ρ‐cymene, phytol, eicosanoic acid, cis,cis,cis‐7,10,13‐hexadeca trienal and α‐irone) and the good antioxidant and antimicrobial activity of Boldo extract (Bonilla & Sobral, ). The second study reported that films based on blended biopolymers (GEL50:CH50), with Boldo extract at 1%, showed good physical properties (more resistant and extensible films, with reduced water vapour permeability and considerable protection against UV light), as well as a potential antioxidant and antimicrobial activity Bonilla & Sobral ().…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, Bonilla & Sobral () developed and characterised active films based on gelatin:chitosan blends, incorporating Boldo extract, at 1%. The first study confirmed six main compounds (1,8‐cineol, ρ‐cymene, phytol, eicosanoic acid, cis,cis,cis‐7,10,13‐hexadeca trienal and α‐irone) and the good antioxidant and antimicrobial activity of Boldo extract (Bonilla & Sobral, ). The second study reported that films based on blended biopolymers (GEL50:CH50), with Boldo extract at 1%, showed good physical properties (more resistant and extensible films, with reduced water vapour permeability and considerable protection against UV light), as well as a potential antioxidant and antimicrobial activity Bonilla & Sobral ().…”
Section: Introductionmentioning
confidence: 75%
“…To our knowledge, research on the application of active films to inhibit the undesirable growth of microorganisms and fat oxidation, in sliced Prato cheese during storage, is limited. In this sense, Bonilla & Sobral () previously reported the identification of components (using GC‐MS profile), the antioxidant activity (using three different assays) and antimicrobial activity (against Escherichia coli and Staphylococcus aureus ) of Boldo extract, among others. Moreover, Bonilla & Sobral () developed and characterised active films based on gelatin:chitosan blends, incorporating Boldo extract, at 1%.…”
Section: Introductionmentioning
confidence: 99%
“…2). According to Bonilla et al (2012), films made from proteins and carbohydrates are excellent barriers to oxygen, because of their tightly packed, ordered hydrogen-bonded network structure. Thus, oxidation could be effectively reduced by selecting films and coatings of limited oxygen permeability.…”
Section: Characterisation Of Coating-forming Solutionsmentioning
confidence: 99%
“…However, their high content of unsaturated fatty acids makes them susceptible to oxidative rancidity if stored sub-optimally or for too long, especially when shelled (Shahidi & John, 2013). The oxidation process leads to quality deterioration of the nuts (rancid odours and flavours, a decrease in nutritional quality and the formation of potentially toxic compounds) (Atar es & Chiralt, 2016), being the most common indicators of lipid rancidity, the peroxide value (PV) and hexanal levels (Bonilla et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation